Efficacy of Early Enteral Immunonutrition on Immune Function and Clinical Outcome for Postoperative Patients With Gastrointestinal Cancer. Issue 4 (20th December 2017) - Luo, Zhenzhen; Wang, Junxia; Zhang, Zhen; Li, Hong; Huang, Lan; Qiao, Yamin; Wang, Dan; Huang, Jingjing; Guo, Luwei; Liu, Jinbo; Liu, Yanhua; Zhang, Yi
Abstract: Background : Nutrition support is crucial for patients with gastrointestinal (GI) cancer after the operation. However, the controversy over the application of parenteral nutrition (PN) and early enteral immunonutrition (EEIN) has no determinate conclusion. Materials and Methods : We compared the effects of PN and EEIN on the postoperative nutrition condition, immune status, inflammation level, long‐term survival, and quality of life of the patients with GI cancer. Seventy‐eight patients were randomly divided into the PN group (n = 44) or EEIN group (n = 34). After an 8‐day nutrition treatment, clinical and immunological parameters were evaluated. Results : The EEIN group had a significantly shorter hospital stay and higher body mass index level on postoperative day 30 than those in the PN group ( P < .05). However, total hospital cost and incidences of short‐term postoperative complications had no significant difference ( P > .05). The percentages of CD4 +, natural killer, and natural killer T lymphocyte cells and the ratio of CD4 + /CD8 + in peripheral blood were significantly increased. Compared with the PN group, the EEIN group had a higher expression of activated cell surface markers such as CD27 and CD28. In addition, the secretion of interleukin (IL)–2 and interferon‐γ was significantly higher, and the secretion of tumor necrosis factor–α and IL‐10 was lower. Complication‐free survival in the EEIN group were longer than those in the PN group ( P = .04). Conclusion : EEIN is superior to PN in improving nutrition status, enhancing immune function, and elevating quality of life.